Investigating the Persistence of Federal Government Publications in Academic Former Full Depository Libraries in Canada - Campbell, Graeme; Lake, Michelle; McGoveran, Catherine (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – The Depository Services Program (DSP) provided printed Government of Canada publications to libraries until the termination of its distribution program in 2013. Full Depository Libraries (FDLs) received all eligible publications distributed by the DSP automatically. This study endeavours to determine whether academic library members of the Canadian Association of Research Libraries (CARL) that were formerly FDLs have maintained their print, federal government holdings since 2013; and what the results of the data collected in this study reveal about access to government information in Canada more broadly.Methods – The study identified a sample of 100 monographs distributed to FDLs via the DSP between 1979 and 2009. Each monograph was then searched for in the public catalogues of former FDL CARL member libraries to determine current holdings.Results – Most libraries included in the sample did not have records of all 100 publications, but every publication was located in at least 5 libraries and 12 publications were found in all libraries included in the study. Of the libraries in our sample, 1/3 had retained more than 90 of 100 publications, and 3/4 had retained at least 80.Conclusion – The redundancy that was a cornerstone of the DSP network still exists to a certain extent and should be leveraged to ensure retention and access to these essential materials for years to come. Existing collaborations and partnerships are well positioned to support a pan-Canadian discussion about preservation of and access to historical federal government information in Canadian libraries and library networks.